Growth, Nutrient Retention, Waste Output, and Antioxidant Capacity of Juvenile Triangular Bream (Megalobrama terminalis) in Response to Dietary Selenium Yeast Concentration - Yubo Wu; Hengjia Ma; Donghuan Fu; Hui Zhu; Xiujuan Wang; Xing Ren (Aquaculture Nutrition)
An 8-week feeding trial was conducted to investigate the effects of different dietary selenium yeast levels on growth, nutrient retention, waste output, and antioxidant capacity of juvenile triangular bream (Megalobrama terminalis). Five isonitrogenous (320 g/kg crude protein) and isolipidic (65 g/kg crude lipid) diets were formulated, with supplementation of graded levels of selenium yeast at 0 (diet Se0), 1 (diet Se1), 3 (diet Se3), 9 (diet Se9), and 12 g/kg (diet Se12). No significant differences were found in initial body weight, condition factor, visceral somatic index, hepatosomatic index, and whole body contents of crude protein, ash, and phosphorus among fish fed different test diet. The highest final body weight and weight gain rate were found in fish fed diet Se3. The specific growth rate (SGR) is closely related to dietary selenium (Se) concentrations with a relationship described as SGR=–0.0043 Se2+0.1062 Se+2.661. Higher feed conversion ratio was found, while lower retention efficiencies of nitrogen and phosphorus were found in fish fed diets Se1, Se3, and Se9 than in fish fed diet Se12. Contents of selenium in whole body, vertebra, and dorsal muscle increased with dietary supplementation of selenium yeast increased from 1 mg/kg to 9 mg/kg. Lower nitrogen and phosphorous waste was found in fish fed diets Se0, Se1, Se3, and Se9 than in fish fed diet Se12. Fish fed diet Se3 exhibited the highest activities of superoxide dismutase, glutathione peroxidase, and lysozyme while the lowest malonaldehyde content in both the liver and kidney. Our results showed that the optimal dietary selenium requirement for triangular bream should be 12.34 mg/kg based on the nonlinear regression on SGR, and fish fed diet Se3 in which selenium concentration (8.24 mg/kg) was close to the optimal requirement displayed the best growth performance, feed nutrient utilization, and antioxidant capacity.